Tracking the financial flows of Indonesia's COVID-19 vaccination program. - Olivia Herlinda; Ayudina Larasanti; Sinta Amalia Kusumastuti Sumulyo; Sayyid Muhammad Jundullah; Indra Yudha Mambea (PLOS Global Public Health)
Despite available funding mechanisms for COVID-19 vaccination programs, disparities persisted in certain areas. This study aimed to track the sources, allocation, and utilization of provincial and district-level government expenditures on the COVID-19 vaccination program in Indonesia to identify financial gaps affecting vaccination coverage. This study used a mixed-method approach to track the expenditure of Indonesia's COVID-19 vaccination program in 2021 and 2022 using the System of Health Accounts (SHA) framework. We collected expenditure data and conducted focus group discussions and in-depth interviews with government representatives from targeted provinces and districts. Case studies were conducted in four Provincial Health Offices (PHOs) and four District Health Offices (DHOs) in Indonesia. The results of expenditure tracking show significant variation in the expenditure for the COVID-19 vaccination program across subnational levels, based on factors such as fiscal capacity, political commitment, national and regional priorities, access challenges, geography, existing immunization infrastructure, and private sector engagement. Despite these variations, most of the programs were primarily funded by the National or Regional Budget, with subnational governments highly dependent on central government budget transfers. The largest expenditures generally included funding for the cold chain, distribution, vaccinator incentives, and per diem.This study found that Indonesia's complex health financing mechanism, coupled with limited fiscal capacity, struggles to ensure equitable vaccination delivery, especially in underserved areas. The budget transfer process from central to subnational levels is inadequate to account for vulnerabilities like geographical challenges. These disparities underscore the need for more coordinated and flexible health financing mechanisms during pandemics. Developing resource allocation guidelines and improving national-to-local resource distribution during health crises are essential for better outcomes.